Implementation of E-learning Through Teacher’s Self-Efficacy and Their Technology Readines - Taufik Hidayat (Sultan Publisher, 2024)
E-Learning Implementation in schools has been compulsory especially in the era of post-Covid19. Teachers should have an ability to deliver the education to their students towards e-learning because of the government’s requirement these days to avoid infection that should be done through distance learning. In this article, several factore were hinted as contributed factor for teacher to adapt newer technology especially in e-learning adaption. Self-efficacy is believed the important factor because it could raise their satisfaction toward their jobs as an educator. Other than that, technology readiness that divided into four main factors, i.e. optimism, innovativeness, discomfort and insecurity were also contributed as meaningful factors to achieve better education through e-learning adaptation. Three variables, namely self-efficacy, optimism and innovativeness factors had positive impact, where the other two, specifically discomfort and insecurity had negative impact that could affect e-learning implementation.